Odpowiedź :
b)
[tex]3x - y = 5 \ \ \rightarrow \ \ y = 3x-5\\(x+1)(x+1)-y=x(x+1)\\\\(x+1)^{2}-(3x-5) = x^{2}+x\\\\x^{2}+2x+1 -3x+5 = x^{2}+x\\\\-x+6 = x\\\\-x-x = -6\\\\-2x= -6 \ \ /:(-2)\\\\\underline{x = 3}\\\\y = 3x-5 = 3\cdot3-5 = 9-5\\\\\underline{y = 4}[/tex]
[tex]\{x = 3\\\{y = 4[/tex]
c)
[tex]\frac{x-1}{2}+\frac{y+1}{3} = 3 \ \ |\cdot6\\\frac{x+1}{3}-\frac{y-2}{6} = 2 \ \ |\cdot 6[/tex]
[tex]3(x-1) + 2(y+1) = 18\\2(x+1) -(y-2) = 12[/tex]
[tex]3x-3 +2y+2 = 18\\2x+2-y+2 = 12[/tex]
[tex]3x+2y-1 = 18\\2x-y+4 = 12[/tex]
[tex]3x+2y = 19\\2x-y = 8 \ \ |\cdot2[/tex]
[tex]3x + 2y = 19\\4x-2y = 16\\------- + (obustronnie \ dodajemy)\\7x = 35 \ \ /:5\\\underline{x = 5}\\\\y = 2x-8 = 2\cdot5 - 8 = 10-8\\\underline{y = 2}[/tex]
[tex]\{x = 5\\\{y = 2[/tex]